The Role of Insulin-Like Growth Factor-I in the Physiopathology of Hearing - Murillo-Cuesta, Silvia; Rodríguez-de La Rosa, Lourdes; Lassaleta, Luis; Cediel, Rafael; Varela-Nieto, Isabel (Frontiers in Molecular Neuroscience, 2011)
Insulin like growth factor I (IGF-I) belongs to the family of polypeptides of insulin, which play a central role in embryonic development and adult nervous system homeostasis by endocrine, autocrine and paracrine mechanisms. IGF-I is fundamental for the regulation of cochlear development, growth and differentiation, and its mutations are associated with hearing loss in mice and men. Low levels of IGF-I have been shown to correlate with different human syndromes showing hearing loss and with presbyacusis. Animal models are fundamental to understand the genetic, epigenetic, and environmental factors that contribute to human hearing loss. In the mouse, IGF-I serum levels decrease with ageing and there is a concomitant hearing loss and retinal degeneration. In the Igf1-/- null mouse, hearing loss is due to neuronal loss, poor innervation of the sensory hair cells and age-related stria vascularis alterations. In the inner ear, IGF-I actions are mediated by intracellular signaling networks, RAF, AKT and p38 MAPK protein kinases modulate the expression and activity of transcription factors, as AP1, MEF2, FoxM1 and FoxP3, leading to the regulation of cell cycle and metabolism. Therapy with rhIGF-I has been approved in humans for the treatment of poor linear growth and certain neurodegenerative diseases. This review will discuss these findings and their implications in new IGF-I-based treatments for the protection or repair of hearing loss.